Pengaruh Tata Letak Terhadap Kepuasan Pelanggan Ritel - Supariyani, Emmy; Marpaung, Bintang Sahala (LPPM Institut Bisnis dan Informatika Kesatuan, 2013)
Layout of a store is very influential to customers’ convenience in shopping. Store layout is defined as setting the selling and non-selling, path, display shelf, placement of goods and tools connected each other that unite in a structure.This study is done to find out and get a clear picture concerning the effect of grid line layout to customers’ satisfaction of foodmart Ekalokasari Bogor. This study is also to know the average value and the relationship closeness between grid line layout and customers’ satisfaction at Foodmart Ekalokasari bogor. The result of this research shows that customers’ perception on grid line layout at Foodmart Ekalokasari Bogor nowadays is good; by using average analysis (performance – importance), it’s gotten the performance average value is 4223. While the importance average value is 4132 where the table of scale range of average analysis is good. Based on the research conducted, it can be known that grid line layout contributes 42,9% to customers’ satisfaction at Foodmart Ekalokasari Bogor. Based on the analysis, it can be concluded that grid line layout at Foodmart Ekalokasari Bogor has influence towards cutomers’ satisfaction. This can be proved based on the contribution of grid line layout towards customers’ satisfaction at Foodmart Ekalokasari Bogor. Keywords: grid line layout; customers’ satisfaction, retailers